Discourse analysis beyond the speech event - Wortham, Stanton, 1963-; Reyes, Angela, 1970- (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Discourse Analysis beyond the Speech Event introduces a new approach to discourse analysis. In this innovative work, Wortham and Reyes argue that discourse analysts should look beyond fixed speech events and consider the development of discourses over time. Drawing on theories and methods from linguistic anthropology and related fields, this book is the first to present a systematic methodological approach to conducting discourse analysis of linked events, allowing researchers to understand not only individual events but also the patterns that emerge across them. This new edition
Discourse analysis across events -- Central tools and techniques -- Discourse analysis of ethnographic data -- Discourse analysis of archival data -- Discourse analysis of new media data -- Discourse analysis of contemporary nationalist new media -- Conclusions.
OCLC-licensed vendor bibliographic record.
Keywords: Discourse analysis; Perspective (Linguistics); Speech acts (Linguistics); Communication -- Methodology; LANGUAGE ARTS & DISCIPLINES / General; LANGUAGE ARTS & DISCIPLINES / Communication; LANGUAGE ARTS & DISCIPLINES / Linguistics